Knowledge, Beliefs and Attitudes of Patients and the General Public towards the Interactions of Physicians with the Pharmaceutical and the Device Industry: A Systematic Review. - Racha Fadlallah; Hala Nas; Dana Naamani; Fadi El-Jardali; Ihsan Hammoura; Lina Al-Khaled; Hneine Brax; Lara Kahale; Elie A Akl (PLoS ONE)
Objective To systematically review the evidence on the knowledge, beliefs, and attitudes of patients and the general public towards the interactions of physicians with the pharmaceutical and the device industry. Methods We included quantitative and qualitative studies addressing any type of interactions between physicians and the industry. We searched MEDLINE and EMBASE in August 2015. Two reviewers independently completed data selection, data extraction and assessment of methodological features. We summarized the findings narratively stratified by type of interaction, outcome and country. Results Of the 11,902 identified citations, 20 studies met the eligibility criteria. Many studies failed to meet safeguards for protecting from bias. In studies focusing on physicians and the pharmaceutical industry, the percentages of participants reporting awareness was higher for office-use gifts relative to personal gifts. Also, participants were more accepting of educational and office-use gifts compared to personal gifts. The findings were heterogeneous for the perceived effects of physician-industry interactions on prescribing behavior, quality and cost of care. Generally, participants supported physicians' disclosure of interactions through easy-to-read printed documents and verbally. In studies focusing on surgeons and device manufacturers, the majority of patients felt their care would improve or not be affected if surgeons interacted with the device industry. Also, they felt surgeons would make the best choices for their health, regardless of financial relationship with the industry. Participants generally supported regulation of surgeon-industry interactions, preferably through professional rather than governmental bodies. Conclusion The awareness of participants was low for physicians' receipt of personal gifts. Participants also reported greater acceptability and fewer perceived influence for office-use gifts compared to personal gifts. Overall, there appears to be lower awareness, less concern and more acceptance of surgeon-device industry interactions relative to physician-pharmaceutical industry interactions. We discuss the implications of the findings at the patient, provider, organizational, and systems level.